2006
DOI: 10.1109/tap.2006.874323
|View full text |Cite
|
Sign up to set email alerts
|

Single and Double Layer Planar Multiband PIFAs

Abstract: This is an accepted pre-published version of this paper.© 2007 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.The link to this paper on IEEE Xplore® is http://ieeexplore.ieee.org/xpl/art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Several studies have reported applications and technologies of the multiband antenna design, including the internal quad-band handset antenna of compact size [2], single and double layer multiband planar inverted-F antenna (PIFA) [3], multi-resonant monopole antenna [4], and multiband multiple ring monopole antenna [5]. Different from the multiband antenna, broadband antennas have been designed for high speed transmission rates and high capacity broadband services.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported applications and technologies of the multiband antenna design, including the internal quad-band handset antenna of compact size [2], single and double layer multiband planar inverted-F antenna (PIFA) [3], multi-resonant monopole antenna [4], and multiband multiple ring monopole antenna [5]. Different from the multiband antenna, broadband antennas have been designed for high speed transmission rates and high capacity broadband services.…”
Section: Introductionmentioning
confidence: 99%
“…This antenna possesses advantages such as high gain, narrow beam, and low side lobes, but has not received much attention and found popular applications since it was first presented by Kraus[1]. Literatures investigating it are limited, e.g., Conti et al [2] reported a microstrip version of the array, and H. Nakano [3]- [11] analyzed its radiation characteristics and introduced some extensions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PIFAs can be modified to operate over multiple frequency bands by using, for example, parasitic antenna elements and/or slitting the antenna element to form several paths for surface currents. Recently, PIFA structures covering the frequency range of six telecommunication standards have been reported [8], [9]. A common approach to tuning the operating frequency of a PIFA is to electrically reconfigure a short circuit connection with an external tuning circuit.…”
Section: Introductionmentioning
confidence: 99%